2019
DOI: 10.1093/nar/gkz1151
|View full text |Cite
|
Sign up to set email alerts
|

Spatially multiplexed RNA in situ hybridization to reveal tumor heterogeneity

Abstract: Multiplexed RNA in situ hybridization for the analysis of gene expression patterns plays an important role in investigating development and disease. Here, we present a method for multiplexed RNA-ISH to detect spatial tumor heterogeneity in tissue sections. We made use of a microfluidic chip to deliver ISH-probes locally to regions of a few hundred micrometers over time periods of tens of minutes. This spatial multiplexing method can be combined with ISH-approaches based on signal amplification, with bright fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 104 publications
1
18
0
Order By: Relevance
“…DNA methylation heterogeneity across cells was linked to splicing variability during differentiation of induced pluripotent stem cells in another study 18 . Multiplexed RNA in situ hybridization revealed high spatial heterogeneity of biomarker gene expression in tumor tissues, suggesting the potential application of spatial heterogeneity as a complementary approach for breast cancer subtype differentiation 19 . Thus intercellular/ interregional gene expression heterogeneity has functional consequences and clinical applications, underscoring its importance.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation heterogeneity across cells was linked to splicing variability during differentiation of induced pluripotent stem cells in another study 18 . Multiplexed RNA in situ hybridization revealed high spatial heterogeneity of biomarker gene expression in tumor tissues, suggesting the potential application of spatial heterogeneity as a complementary approach for breast cancer subtype differentiation 19 . Thus intercellular/ interregional gene expression heterogeneity has functional consequences and clinical applications, underscoring its importance.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al demonstrated that seqFISH is a powerful tool to study and gain a snapshot of the regulatory gene expression dynamics in T-cell maturation [ 83 ]. More recently, Voith von Voithenberg et al combined microfluidics technology with multiplexed smFISH to study tumour heterogeneity in breast cancer; they demonstrated that multiplexed smFISH can be further optimized from different angles [ 84 ].…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…In contrast to genes and proteins that are highly differentially expressed in cancer, the validation of low abundance genes as diagnostic and prognostic tools in tumor pathology is a big challenge. Branched probe-based or enzymatic amplification RNA-ISH methods for the detection and quantification of transcripts in FFPE tissues [55] may be ideally suited to evaluate cancer biomarker candidates on the mRNA level. Given the huge amount of survival-related gene expression data in the TCGA database, systematic and comprehensive gene expression profiling of such candidate genes are necessary to better understand the complex regulatory network along tumor progression, which may lead to new therapeutic strategies to treat aggressive chRCC.…”
Section: Discussionmentioning
confidence: 99%